Inhibiting two cellular mutant epidermal growth factor receptor tyrosine kinases by addressing computationally assessed crystal ligand pockets. (6th February 2019) - Lee, Jia-Hau; Lin, Wei-Chen; Wen, Tsung-Kai; Wang, Chihuei; Lin, Ying-Ting
Aim: Blocking receptor tyrosine kinases is a useful strategy for inhibiting the overexpression of EGFR. However, the quality of crystal pocket is an essential issue for virtually identifying new leads for surviving resistance cancer cells.Results: With the examinating crystal pocket quality by the self-docking root-mean-square deviation (RMSD) calculation, we used the two best kinase pockets of mutant EGFR kinases, T790M/L858R and G719S, for virtual screening. After sorting all the docking poses of the 57, 177 library compounds by consensus scores, three evidently blocked cellular EGFR phosphorylation in the H1975 and SW48 cell lines.Conclusion: The computationally assessed qualities of crystal pockets of crystal EGFR kinases can help identify new cellular active and target-specific ligands rapidly and at low cost.